PACLITAXEL DISPOSITION STUDIES USING P-GP INHIBTOR & INDUCER BY SINGLE PASS INTESTINAL PERFUSION IN RATS - P.Shashikanth; Chandra Mohan, P.; Karunakar, K; Raviteja Sagi, S M (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present research work aims to study the intestinal transport of Paclitaxel and to predict its human intestinal permeability and fraction absorbed using SPIP Permeability Coefficient and the effect of P-gp modulators on Paclitaxel were observed in anaesthetized rats. Methods: Jejunal segment was used for performing Single Pass Intestinal Perfusion. The rationale for the selection of jejenum is due to the overexpression of P-glycoprotein when compared with other segments. Drug solution (150µg/ml) in phosphate buffer saline was perfused at a flow rate of 0.2ml/min.Besides,P-gp inhibitor verapamil(200 µg/ml) and inducer Rifampicin (60mg/ml) were coperfused with Paclitaxel to detect its disposition characteristics affected by P-gp .Drug concentrations in samples were analyzed using HPLC. Stability studies were conducted to ensure the loss of Paclitaxel due to absorption. Results: The effective permeability value of Paclitaxel (150µg/ml) in the jejunal segment was found to be lower due to the efflux mediated by P-gp.When coperfused with verapamil its permeability significantly enhanced as it is a P-gp inhibitor and vice versa with Rifampicin which is a P-gp inducer. Subsequently the human intestinal permeability was estimated considering Peff(human) =1.04 Peff(rat)-0.0003. Conclusion: P-Glycoprotein mediated drug resistance is one of the serious limitations of Paclitaxel efficacy and jejunal segment is found to have major MDR expression. The Peff value of Paclitaxel was found to be increased upon the Coperfusion with verapamil and similarly reduced with Rifampicin which are inhibitors & inducers respectively indicating Paclitaxel is efficiently transported by P-gp. Hence, Paclitaxel satisfies all the prerequisites to be a P-gp substrate. Keywords: Paclitaxel, Intestinal permeability, Single pass intestinal perfusion, P-glycoprotein, RP-HPLC.